2020
DOI: 10.3390/mi11121076
|View full text |Cite
|
Sign up to set email alerts
|

Composites, Fabrication and Application of Polyvinylidene Fluoride for Flexible Electromechanical Devices: A Review

Abstract: The technological development of piezoelectric materials is crucial for developing wearable and flexible electromechanical devices. There are many inorganic materials with piezoelectric effects, such as piezoelectric ceramics, aluminum nitride and zinc oxide. They all have very high piezoelectric coefficients and large piezoelectric response ranges. The characteristics of high hardness and low tenacity make inorganic piezoelectric materials unsuitable for flexible devices that require frequent bending. Polyvin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 168 publications
(271 reference statements)
1
60
0
Order By: Relevance
“…PVDF and PVDF based nanocomposite are very useful to the electromechanical application due to the piezoelectrical properties of the polymer 65 . However, various carbon and semiconducting nanomaterials can be used to tune the dielectric, thermal and mechanical strength of PVDF composite.…”
Section: Resultsmentioning
confidence: 99%
“…PVDF and PVDF based nanocomposite are very useful to the electromechanical application due to the piezoelectrical properties of the polymer 65 . However, various carbon and semiconducting nanomaterials can be used to tune the dielectric, thermal and mechanical strength of PVDF composite.…”
Section: Resultsmentioning
confidence: 99%
“…The research idea is based on the incorporation of Magnesium into PVDF structure by NIPS using different weight ratios of PVDF/MgCl2, DMF solvent and denoised water as no solvent. The results of characterization using XRD, FTIR [19]. Other research work by have been found the PVDF crystal change to higher value percentages of β phases 80%, 71% and 84%, this is due to inclusion of Cloisite 30B and MWCNT which increase the reinforcement of the surface [20].…”
Section: Introductionmentioning
confidence: 96%
“…As a semi-crystalline polymer, polyvinylidene fluoride (PVdF) consists of five main phase structures, namely α, β, γ, δ, and ε phases [ 1 , 2 , 3 , 4 , 5 , 6 ]. Owing to the specific conformation of the carbon chain backbone, considerable attention has been paid to the β structure of PVdF, which is known to have piezo-, pyro-, and ferroelectric applications [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a semi-crystalline polymer, polyvinylidene fluoride (PVdF) consists of five main phase structures, namely α, β, γ, δ, and ε phases [ 1 , 2 , 3 , 4 , 5 , 6 ]. Owing to the specific conformation of the carbon chain backbone, considerable attention has been paid to the β structure of PVdF, which is known to have piezo-, pyro-, and ferroelectric applications [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Unlike piezoelectric ceramics, piezoelectric polymers such as PVdF are flexible, which may be crucial in the development of wearable electronic mobile devices in the future [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation